“That’ll Teach Them”: Investigating the Soft Power Conversion Model through the Case of Russian Higher Education - A. Crowley-Vigneau; A. A. Baykov; E. Kalyuzhnova (Высшее образование в России, 2022)
While the international environment remains characterized by the desire of states to strengthen their position, the literature has revealed a growing preference for soft power instruments over military intervention. Higher education has been repurposed as a tool to achieve foreign policy goals, with many states embracing the international norm on world-class universities in an attempt to improve their international competitiveness and their image abroad. This paper considers the soft power conversion model of higher education and attempts to determine its effectiveness through a case study devoted to Russian Higher Education. A survey of foreign students starting their studies and of another finishing their studies in three leading Russian universities reveals that receiving a higher education in Russia may contribute to aligning students’ positions with the Russian perspective on international issues diffused in these universities as was confirmed by surveying a control group of Russian students. These preliminary findings suggest that the benefits of internationalizing national higher education systems are not just reserved to the norm initiators (US, UK) but extend to second wave norm adopters (Russia, China).